PERKIRAAN TIMBULAN SAMPAH KOTA JAMBI TAHUN 2015. - Guntar Marolop S (Universitas Batanghari Jambi, 2015)
Garbage timbulan estimation data of a city is important data that must exist for the city waste management planning of comprehensive and integrated from upstream to downstream. Timbulan saampah estimates the city preferably there should be every year or at least 5 years. Timbulan estimates data trash city of Jambi is data in 2005.To estimate the timbulan of garbage city are obtained by means of survey timbulan the garbage using SNI 19-3964-1994Timbulan Jambi city residents as much as junk 1755.05 m³/day. Its characteristics 32.98% organic and inorganic 67.02%. The composition of the organic waste of 32.98% and inorganic garbage of 67,02%.Keywords: garbage timbulan